2019
DOI: 10.1111/all.13870
|View full text |Cite
|
Sign up to set email alerts
|

Pruritus in ordinary scabies: IL‐31 from macrophages induced by overexpression of thymic stromal lymphopoietin and periostin

Abstract: Abbreviations: Ab, antibody; AD, atopic dermatitis; Ag, antigen; Arg1, arginase 1; CCR4, C-C chemokine receptor type 4; CD, cluster of differentiation; CXCR3, C-X-C chemokine receptor type 3; ELISA, enzyme-linked immunosorbent assay; IENFD, intraepidermal nerve fiber density; Ig, immunoglobulin; IL, interleukin; IL-7Rα, IL-7 receptor α; iNOS, inducible nitric oxide synthase; OSMRβ, oncostatin M receptor β; PAR-2, protease-activated receptor 2; PGP9.5, protein gene product 9.5; pM, peritoneal macrophages; TARC,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(60 citation statements)
references
References 49 publications
3
56
1
Order By: Relevance
“…Under such abundant triggers and regulators, TSLP succeeds in sensing both exogenous and endogenous dangerous signals and exacerbating allergic inflammation as an alarm via activating its downstream responders, namely naive Th cells, Th2 cells, ILC2s, and myeloid dendritic cells 72,80‐82 . TSLP activates myeloid DCs (mDCs) via ligation to its heterodimer receptor on mDCs and subsequently upregulates the expression of the co‐stimulatory molecule OX40L, namely the ligand for OX40 on CD4 + T cells, which results in the induction of Th2 differentiation 83 .…”
Section: Epithelium‐derived Tslpmentioning
confidence: 99%
“…Under such abundant triggers and regulators, TSLP succeeds in sensing both exogenous and endogenous dangerous signals and exacerbating allergic inflammation as an alarm via activating its downstream responders, namely naive Th cells, Th2 cells, ILC2s, and myeloid dendritic cells 72,80‐82 . TSLP activates myeloid DCs (mDCs) via ligation to its heterodimer receptor on mDCs and subsequently upregulates the expression of the co‐stimulatory molecule OX40L, namely the ligand for OX40 on CD4 + T cells, which results in the induction of Th2 differentiation 83 .…”
Section: Epithelium‐derived Tslpmentioning
confidence: 99%
“…Periostin, substance P, and hemosiderin, but not thymic stromal lymphopoietin, are correlated with IL-31 expression by macrophages Thymic stromal lymphopoietin and periostin promote M2 skewing (Furudate et al, 2016;Han et al, 2013) and IL-31 generation from M2 macrophages (Hashimoto et al, 2019b). Epidermal expression of thymic stromal lymphopoietin was not enhanced in the SD lesions compared with healthy controls (t-test, P ¼ 0.182).…”
Section: Lesional Expression Of Il-31ra and Osmrbmentioning
confidence: 92%
“…Macrophages are generally divided into two groups: M1 and M2 (Wang et al, 2014). Our group previously reported that M2 macrophages are capable of generating IL-31 (Hashimoto et al, 2019b). Thus, we examined the expression of an M2 marker, CD163, by CD68(þ) cells.…”
Section: Cd68(d)/cd163(d) Macrophages Express Il-31 and Correlate Witmentioning
confidence: 99%
See 1 more Smart Citation
“…Th2 immunity is dominant in scabies and is complemented by a heavy inflow of IL-31(+) M2 macrophages [73]. Proteases from scabies mite stir epidermal KCs to express TSLP.…”
Section: P Acnesmentioning
confidence: 99%